Analisis Pesan Moral terhadap Sikap Wanita Tarim dalam Buku Bidadari Bumi 9 Kisah Wanita Salehah - Astika, Firliana Putri; Kamalludin, Kamalludin; Anggrayni, Dewi (Universitas Ibn Khaldun Bogor, 2025)
The novel is a source of learning in the form of print media. This phenomenon has become a trend for women in general in this era of problems with Muslim women's groups, giving rise to a negative impression of people's views on social life, where women compete in world affairs in such a way that they forget about the afterlife in order to appear in world affairs in such a way that they forget about the afterlife in order to appear fashionable. This study aims to find out that Islamic life can be exemplified by a true story, namely the novel 'Bidadari Bumi 9 Stories of Salehah Women' written by Halimah Alaydrus. Researchers used a qualitative approach to the type of library research (library research). Data collection instrument using the documentation method. While data analysis using techniques content analysis (content analysis). Based on the results of the study, the values of the moral message of Islamic education contained in the book are divided into three, namely: (1) the values of aqidah: belief in Allah, His angels, His Book, His Apostles, the Day of Judgment and Square Good and Bad Fate; (2) the values of worship, mahdhah worship: prayer worship, hajj worship, and seeking knowledge, and mahdhah passion:stay in touch, giving charity, and visiting the sick; and (3) moral values: morals towards Godhow much monotheism of God, piety, prayer, dhikrullah, tawakkal and repentance, morals towards others: ta'awun (help each other), forgiveness, and testament in the truth, and morals towards oneself: patience, gratitude, tawadhu', trust or honest, and syaja'ah (dare to tell the truth).